Gender-modulated influence of BDNF concentration and Val66Met polymorphism on cognitive outcomes in chronic limb ischemia patients - Chyrek-Tomaszewska, Aleksandra; Popiołek, Alicja; Stachowicz-Karpińska, Agnieszka; Budzyński, Jacek; Linkowska, Katarzyna; Kozakiewicz, Mariusz; Szelągowski, Adam; Borkowska, Alina; Bieliński, Maciej (Frontiers in Endocrinology, 2024)
While numerous studies have established associations between brain-derived neurotrophic factor (BDNF) and cognitive functioning, limited research has delved into the role of BDNF concerning cognitive outcomes in atherosclerosis-related conditions. This study aimed to investigate the correlations between cognitive performance, serum BDNF levels, and the BDNF Val66Met polymorphism in individuals diagnosed with chronic limb ischemia (CLI).The study encompassed 159 CLI patients (52 females, 107 males) aged 59-73 years. Genetic analysis involved assessing the BDNF Val66Met single-nucleotide polymorphism using a TaqMan SNP Genotyping Assay and the ViiA™ 7 Real-Time PCR System. Serum BDNF levels were quantified. Cognitive functioning was evaluated through a computerized battery of tests, including the simple reaction test (SRT) for speed and accuracy assessment, verbal memory test (VMT) for short and long-term memory evaluation, and the GoNoGo test for cognitive control and inhibition. Results Gender differences in cognitive performance were observed, with women excelling in VMT, while men demonstrated superior performance in SRT and the GoNoGo test. No statistically significant differences were noted between the Met/Met or Met/Val and Val/Val subgroups. However, notable differences emerged in female Met carriers, exhibiting superior VMT scores but more incorrect Go responses in the GoNoGo test. Conversely, female Val homozygotes showed significantly more incorrect NoGo responses compared to male Val homozygotes. In men carrying the Met allele, higher BDNF concentrations correlated with improved GoNoGo test results (r = 0.248, p = 0.01). Conversely, in women with the Val/Val variant, lower BDNF concentrations were associated with better VMT scores.This study underscores the sex-specific impact of BDNF serum levels and the BDNF polymorphism on cognitive processes among CLI patients. The findings highlight the nuanced influence of BDNF in shaping cognitive functioning, emphasizing the need for further research into these sexdependent associations.